The formation of environmental sustainability and its consequences of digital technologies in the green economy - Gofurova Lola (THE INNOVATION ECONOMY, 2026)
This article comprehensively analyzes the role of modern digital technologies in the green economy and their impact on the formation of environmental sustainability. The article covers the integration of artificial intelli gence (AI), Internet of Things (IoT), big data (Big Data), digital platforms and blockchain technologies into ecological systems, energy efficiency, automatic waste management, and water and air quality monitoring. The main purpose of the article is to determine the role of digital technologies in the green economy, to conduct a balanced analysis of the opportunities and risks in ensuring environmental sustainability, and to provide scientific recommendations on promising directions in this area